Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00787-014-0588-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal pre-pregnancy risk drinking and toddler behavior problems: the Norwegian Mother and Child Cohort Study

Abstract: Maternal risk drinking may be a risk factor for child behavior problems even if the mother has discontinued this behavior. Whether pre-pregnancy risk drinking is an independent predictor of child behavior problems, or whether a potential effect may be explained by maternal alcohol use during and after pregnancy or other adverse maternal characteristics, is not known. Employing data from the Norwegian Mother and Child Cohort Study (MoBa), longitudinal associations between maternal pre-pregnancy risk drinking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
(92 reference statements)
0
20
0
1
Order By: Relevance
“…Studies related to substance abuse found that pre-pregnancy risk drinking (Knudsen et al 2014) increased IEP, methamphetamine use during pregnancy increases IEP ) and EP (Twomey et al 2013), tobacco exposure during pregnancy (Liu et al 2013) and maternal smoking during child preschool years increases IEP (Paterson et al 2013). One study reported non-significant results to the effect of methamphetamine exposure during pregnancy in EP (Liles et al 2012).…”
Section: Substance Abusementioning
confidence: 90%
“…Studies related to substance abuse found that pre-pregnancy risk drinking (Knudsen et al 2014) increased IEP, methamphetamine use during pregnancy increases IEP ) and EP (Twomey et al 2013), tobacco exposure during pregnancy (Liu et al 2013) and maternal smoking during child preschool years increases IEP (Paterson et al 2013). One study reported non-significant results to the effect of methamphetamine exposure during pregnancy in EP (Liles et al 2012).…”
Section: Substance Abusementioning
confidence: 90%
“…Several studies have reported associations between heavy maternal alcohol use and increased levels of internalizing and externalizing behavior problems and lower social competence among school-age children [46], and adolescents and adults [7, 8]. Maternal risky alcohol use before [9] and during [10] pregnancy has also been linked to early development of behavior problems. However, in studies on toddlers and preschool children, the focus has primarily been on the impact of the father’s heavy alcohol use on toddler behavior problems [1115].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding roles of rare variants in ASD has highlighted the multifactorial etiology of NDDs characterized by pleiotropy (diverse phenotypes from identical genetic factors), genetic heterogeneity (different genes causing same phenotypes), and interactions: Epistasis (between genes) and gene-environment interactions (GxE) (2–10). Evidence also suggests that environmental factors lead to diverse phenotypes, depending upon the developmental timing of exposure (1113). Research to disentangle this complexity requires strategies that specifically incorporate both genetic and environmental factors.…”
mentioning
confidence: 99%